Recent Epidemic of Sal Borer, Hoplocerambyx spinicornis Newm. In South Mandla Division, Madhya Pradesh and Recommendations for Control - Chatterjee, P. N.; Thapa, R. S. (Indian Forester, 1964)
The sal borer, Hoplocerambyx spinicornis Newm., is endemic in South Mandla Forest Division, Madhya Pradesh. Recently, in June, 1963 serious epidemic was reported by the Chief Conservator of Forests, M.P., to the President, Forest Research Institute to suggest some suitable control measures. An entomological party was sent by the President to get a first hand knowledge of epidemic and conditions prevailing there. An account of party’s survey and work on trap-tree operation during 20th-27th June, 1963 along with recommendations for the control of Hoplo are given in this paper.